Metabolic Signatures of Blood Pressure and Risk of Cardiovascular Diseases - Maria Manou; Christos Papagiannopoulos; Christos V. Chalitsios; Alexandros‐Georgios Asimakopoulos; Georgios Markozannes; Monica Bulló; Konstantinos K. Tsilidis; Christopher Papandreou; Ioanna Tzoulaki (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The underlying biological mechanisms linking blood pressure (BP) and cardiovascular diseases (CVD) are only partly understood. We aimed to identify metabolic signatures associated with systolic and diastolic BP and investigate their subsequent association with risk of CVD. Methods and Results The study included 201 742 UK Biobank participants with measurements on 249 metabolic biomarkers. A multistep adaptive elastic net penalized regression with 10‐fold cross‐validation was employed to identify metabolic signatures for systolic BP and diastolic BP. External validation was conducted on 848 participants from the EHS (Epirus Health Study). We further assessed the associations between BP metabolic signatures and incident composite CVD (N=6742), myocardial infarction (N=4192), and stroke (N=2757) in the UK Biobank, using multivariable Cox regression models. The metabolic signatures comprised 31 and 25 metabolites, robustly correlated with systolic BP and diastolic BP, respectively, in both the UK Biobank and the EHS. Following adjustments (including BP), the metabolic signature for systolic BP was positively associated with incident myocardial infarction (hazard ratio [HR], 1.11 [95% CI, 1.07–1.15]) and CVD (HR, 1.07 [95% CI, 1.04–1.10]). Similarly, the metabolic signature for diastolic BP was associated with a higher risk of myocardial infarction (HR, 1.16 [95% CI, 1.12–1.20]) and CVD (HR, 1.09 [95% CI, 1.05–1.12]). The associations between the signatures and stroke were not significant. The metabolic signatures partly mediated the total effect of the BP traits on the risk of myocardial infarction and CVD. Conclusions Our findings may enhance our understanding of the biological mechanisms through which BP affects CVD.